Photodynamic responsiveness of human leukemia Jurkat/A4 cells with multidrug resistant phenotype - Philchenkov, A.A.; Shishko, E.D.; Zavelevich, M.P.; Kuiava, L.M.; Miura, K.; Blokhin, D.Y.; Shton, I.O.; Gamaleia, N.F. (Experimental Oncology, 2014)
Photodynamic therapy (PDT) is considered as a possible alternative approach to overcoming multidrug resistance (MDR). Analysis of cross-resistance to PDT in cells with different MDR pathways and resistance levels seems to be advantageous for elucidating the general mechanisms of cancer cell resistance to various treatment modalities. Aim: The aim of the study was to clarify whether the Jurkat/A4 leukemia cells with MDR phenotype are cross-resistant to PDT. Methods: Human T-cell acute lymphoblastic leukemia line Jurkat and Jurkat/A4 subline with MDR phenotype were used. 5-Aminolevulinic acid (ALA) and Photolon (a complex of chlorine-e6 and polyvinylpyrrolidone; PL) or gold nanocomposite of PL were applied as photosensitizers. The cells were pretreated with photosensitizers and exposed to laser radiation at corresponding wavelengths. The phototoxicity was assessed in trypan blue exclusion test. The hypodiploid cell fraction was analyzed by flow cytometry of propidium iodide-stained cells. Expression of genes related to PDT resistance was analyzed by microarray technique with Affymetrix U133A chips. Results: ALA-mediated PDT resulted in dose-dependent cell death in both lines, the relative photodynamic efficacy in Jurkat/A4 cells being inferior to that in the parental Jurkat cells. There was no correlation between phototoxicity and apoptosis induction both in Jurkat and Jurkat/A4 cells. PL-mediated general phototoxicity in Jurkat cells amounted up to 75% at the maximal photosensitizer dose with about 40% of apoptotic death fraction. PL-phototoxicity in Jurkat/A4 cells was considerably lower. In contrast to Jurkat cells, PL-gold composite did not increase the efficacy of photosensitization as compared to free PL in Jurkat/A4 cells. Conclusions: Multidrug-resistant Jurkat/A4 cells exhibit reduced sensitivity to phototoxic effect in comparison with parental Jurkat cells independently of nature of the photosensitizer being assayed. Key Words: photodynamic therapy, leukemia cells, multidrug resistance, apoptosis.